2018
DOI: 10.9734/jeai/2018/43402
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting Diodes (LED) as Luminous Lure for Adult Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae)

Abstract: The capture of insects through luminous sources can represent another option for integrated pest management (IPM). The purpose of this study was to verify the attractiveness of different-colored Light-Emitting Diodes (LED) on adult Spodoptera frugiperda. The research was conducted at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Some other insects have also been reported to be sensitive to blue light and can be captured by the blue LED traps, such as the white-backed planthopper (Sogatella furcifera), brown planthopper (Nilaparvata lugens), rice weevil (Sitophilus oryzae), angoumois grain moth (Sitotroga cerealella), and thrips [28,33,34]. However, our results were inconsistent with the results of other studies; Zhang et al (2023) found that S. frugiperda preferred UV light [18], and Nascimento et al (2018) and reported that S. frugiperda preferred green light [16,17]. Potential reasons for this discrepancy could include variations in the type of light source, light intensity, duration of light treatment, and the physiological status of the insect [31,32].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Some other insects have also been reported to be sensitive to blue light and can be captured by the blue LED traps, such as the white-backed planthopper (Sogatella furcifera), brown planthopper (Nilaparvata lugens), rice weevil (Sitophilus oryzae), angoumois grain moth (Sitotroga cerealella), and thrips [28,33,34]. However, our results were inconsistent with the results of other studies; Zhang et al (2023) found that S. frugiperda preferred UV light [18], and Nascimento et al (2018) and reported that S. frugiperda preferred green light [16,17]. Potential reasons for this discrepancy could include variations in the type of light source, light intensity, duration of light treatment, and the physiological status of the insect [31,32].…”
Section: Discussioncontrasting
confidence: 97%
“…Defining the sensitive wavelengths of pests and setting the target sensitive light source helps develop efficient, specific, and ecological security light trapping techniques [9]. As with most insects, existing studies indicated that S. frugiperda is sensitive to blue, green, or UV light, albeit with mixed results [12,13,[16][17][18]. Insect spectral sensitivity can affect various life activities, including orientation, navigation, foraging, hunting, courtship, egg-laying, and other behavioral activities [19,20].…”
Section: Introductionmentioning
confidence: 99%